Faktor-Faktor Yang Berhubungan Dengan Status Gizi Remaja Di SMP Muhammadiyah 21 Serbelawan - Athira Demitri; Dwi Ayu Lestari; Wanda Lestari (Jurnal Praba : Jurnal Rumpun Kesehatan Umum, 2024)
Adolescent nutritional status is one of the determinants of the quality of human resources, if deficiencies will cause very serious effects such as failure of physical growth and not optimal development and intelligence. Based on the health profile of North Sumatra Province in 2019, the prevalence of nutritional status in Simalungun district was very thin at 4.12% and obesity at 2.19%. This study aims to determine the factors associated with nutritional status in adolescents at SMP Muhammadiyah 21 Serbelawan.The research design used in this research is an analytic survey with a cross sectional design, with a population of 523 students and a sample size of 84 students selected by proportionate stratified random sampling. The results showed that there was a relationship between the pocket money factor (p value = 0.000 <0.05), food intake (p value = 0.000 <0.05), physical activity (p value = 0.000 <0.05) with nutritional status. So that the results showed that there were 10 (11.9%) students with thin nutritional status, and 33 (39.3%) students with fat nutritional status.The conclusion of this study is that there is a significant relationship between pocket money, food intake, physical activity with the incidence of nutritional status. It is expected for respondents who have less pocket money and nutrient intake to be able to familiarize a healthy diet, by consuming diverse and nutritious foods.